Social networks and health models, methods, and applications - Valente, Thomas W. (New York ; Oxford : Oxford University Press, 2010)
Providing a comprehensive introduction to how social networks influence health behaviours, this book enables researchers to understand how network data are collected and processed; and how to calculate appropriate metrics and models used to understand network influences on health behaviour.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social networks -- Health aspects; Health behavior